Emotional monasticism : Affective piety in the eleventh-century monastery of John of Fécamp - Mancia, Lauren (Book collections on Project MUSE., 2019)
"Historians have long taught that highly emotional Christian devotion, often called 'affective piety', originated in Europe after the twelfth century, and was primarily practiced by communities of mendicants, lay people and women. . Emotional monasticism revises our understanding of its origins, characteristics, and uses in medieval Christianity. The first study of affective piety in an eleventh-century monastic context, this book traces the history of affective devotion through the life and works of the earliest-known writer of emotional prayers, John of Fecamp, abbot of the Norman monastery of Fecamp from 1028 to 1078. It examines John's major work, the Confessio theologica, and looks at the devotional programme of Fecamp's liturgical, manuscript, and intellectual culture, relating it to the monastery's efforts at reform. Finally, it examines John's later medieval legacy at Fecamp, throughout Normandy, and beyond. Exposing the early medieval monastic roots of later medieval affective piety, Emotional monasticism reexamines the importance of John of Fecamp's prayers for the first time since his work was discovered, casting new light on the devotional life of monks in Europe before the twelfth-century, and redefining how medievalists should teach the history of Christianity." -- Back cover.